2020
DOI: 10.1101/2020.08.19.257352
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modular HUWE1 architecture serves as hub for degradation of cell-fate decision factors

Abstract: HECT ubiquitin ligases play essential roles in metazoan development and physiology. The HECT ligase HUWE1 is central to the cellular stress response by mediating degradation of key death or survival factors including Mcl1, p53, DDIT4, and Myc. As a step toward understanding regulation of HUWE1 engagement with its diverse substrates, we present here the cryo-EM structure of HUWE1, offering a first complete molecular picture of a HECT ubiquitin ligase. The ~4400 amino acid residue polypeptide forms an alpha sole… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…Future studies will be required to interrogate which cellular interactors recognize the identified atypical binding site in the BTB domain of MIZ1. A yet unreleased cryo-electron microscopy reconstruction of full-length HUWE1 shows the AS buried, but residues in this region participate in a dynamic intermolecular interface that affects ligase activity (Hunkeler et al, 2020). Although the precise mechanisms and consequences of the conformational dynamics of HUWE1 are still unclear, it is conceivable that regions of HUWE1 other than the AS occupy the binding site we defined in MIZ1.…”
Section: Llmentioning
confidence: 98%
“…Future studies will be required to interrogate which cellular interactors recognize the identified atypical binding site in the BTB domain of MIZ1. A yet unreleased cryo-electron microscopy reconstruction of full-length HUWE1 shows the AS buried, but residues in this region participate in a dynamic intermolecular interface that affects ligase activity (Hunkeler et al, 2020). Although the precise mechanisms and consequences of the conformational dynamics of HUWE1 are still unclear, it is conceivable that regions of HUWE1 other than the AS occupy the binding site we defined in MIZ1.…”
Section: Llmentioning
confidence: 98%
“…Nevertheless, almost at the same time, Hunkeler M. et al obtained the cryo-EM structure of HUWE1 where they described the N -terminal end. According to this study, this end is made up of four Armadillo Repeated Liked Domains (ARLD1–4); a WWE domain; and a “Tower” and HWA (HUWE1 WWE module Associated) domain [ 162 ]. The ARLD2 contains UBA (UBiquitin Associated) domain and UIM (Ubiquitin Interacting Motif) being the first involved in the binding of polyubiquitin chains, whereas the activity of the second is still not clear [ 162 ].…”
Section: Hect Ligasesmentioning
confidence: 99%
“…According to this study, this end is made up of four Armadillo Repeated Liked Domains (ARLD1–4); a WWE domain; and a “Tower” and HWA (HUWE1 WWE module Associated) domain [ 162 ]. The ARLD2 contains UBA (UBiquitin Associated) domain and UIM (Ubiquitin Interacting Motif) being the first involved in the binding of polyubiquitin chains, whereas the activity of the second is still not clear [ 162 ]. Moreover, BH3 domain is inserted in the ARLD3 domain.…”
Section: Hect Ligasesmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, this Research Topic highlights important discoveries in the structure to physiology understanding of E3 ubiquitin ligases, setting the stage to address important yet unanswered questions in the ubiquitin signaling field. These include the determination of the 3D structure of full length E3 ubiquitin ligases, which is now achievable, as the cryo-EM structure of the HECT ligase HUWE1 has shown (Hunkeler et al, 2020); the definition of the entire human ubiquitome; the mechanisms underlying substrate recognition and processing; the regulation of protein ubiquitination in time and space and tissue; the molecular basis for how deregulation of E3 ubiquitin ligases lead to disease. Addressing these questions will be instrumental in order to develop innovative therapeutics.…”
Section: E3 Ubiquitin Ligases: From Structure To Physiologymentioning
confidence: 99%